KINETIC CONTROL OF OXIDATION STATE AT THERMODYNAMICALLY BUFFERED POTENTIALS IN SUBSURFACE WATERS - Washington J.W.; Samarkina L.P.; Chappell K.E.; Endale D.M. (My University, 2004)
Dissolved oxygen (DO) and organic carbon (Corg) are among the highest- and lowest-potential reactants, respectively, of redox couples in natural waters. When DO and Corg are present in subsurface settings, other couples are drawn toward potentials imposed by them, generating a bimodal clustering of calculated redox potentials. Which cluster a couple is drawn toward is determined by whether the couple’s oxidant or reductant is more concentrated. Generally, reactants >10-6M are near equilibrium with their dominant complementary reactant and in a cluster, whereas reactants <10-6M are relatively slow to react and diverge from the clusters. These observations suggest that reactions of higher-potential oxidants with lower-potential reductants commonly proceed simultaneously, regardless of the presence of other potential reactants, with the rates of reaction being determined more by concentration than relative potentials. As DO or Corg decreases, the potential gap separating couples diminishes. In waters having quantifiable concentrations of higher potential oxidants O2 and NO3-, [H2] was not diagnostic of their presence. In the water we analyzed having no quantifiable O2 or NO3-, redox potential calculated with [H2] was similar to potentials calculated for SO42- reduction and methanogenesis. Composite reactions, NO3-→N2 and O2→H2O, are best characterized in multiple steps due to slow reaction of low-concentration intermediates. The [CO] data we report, among the first for groundwater, are high compared to water equilibrated with the atmosphere.